Gold-catalyzed tandem synthesis of bioactive spiro-dipyrroloquinolines and its application in the one-step synthesis of incargranine B aglycone and seneciobipyrrolidine (I). Issue 3 (12th January 2016) - Ma, Can-Liang; Li, Xiao-Hua; Yu, Xiao-Long; Zhu, Xiao-Long; Hu, Yong-Zhou; Dong, Xiao-Wu; Tan, Bin; Liu, Xin-Yuan
Abstract : The Au-catalyzed tandem reaction provided simple and efficient access to spiro-dipyrroloquinolines and incargranine B aglycone and (±)-seneciobipyrrolidine (I ). Abstract : The Au-catalyzed tandem process of aminoalkynes was explored, providing simple and efficient access to richly functionalized dipyrroloquinoline frameworks with good to excellent yields. The reaction exhibits great efficiency and high atom economy in multiple-bond formation for constructing bioactive azaspiro polycyclic molecules with densely multiple stereogenic centers including quaternary carbons, and shows a broad substrate scope and synthetically important functional group tolerance, which have been illustrated in the first one-step synthesis of incargranine B aglycone and seneciobipyrrolidine (I ).